2021
DOI: 10.1002/srin.202000611
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐Induced Martensite Formation and Mechanical Properties of Fe–19Cr–4Ni–3Mn–0.15N–0.15C Austenitic Stainless Steel at Cryogenic Temperature

Abstract: Herein, considerable insight is provided into the evolution of strain‐induced martensite and mechanical properties of Fe–19Cr–4Ni–3Mn–0.15N–0.15C wt% austenitic stainless steel (in short Cr19NC15.15) during deformation at room temperature and cryogenic temperatures. In situ magnetic measurements of the martensite evolution during tensile tests at various temperatures are conducted. The triggering stress σtrigg.γ→α′ required for strain‐induced martensite formation is determined at the minimum in the strain hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The minimum coincides with the first inflection point (IP) of the stress–strain curve and is often used to define the onset of strain-induced α′-martensite formation. However, from previous investigations into austenitic CrMnNi steels, it is known that a small strain-induced martensite fraction of 2–5 vol.% already exists in the minimum of the strain hardening curve [ 44 , 45 , 46 ]. Once the minimum in the strain hardening curve was exceeded, the curve increased progressively owing to the strong effect of strain-induced martensite on the strain hardening rate during ongoing tensile deformation (stage II).…”
Section: Discussionmentioning
confidence: 99%
“…The minimum coincides with the first inflection point (IP) of the stress–strain curve and is often used to define the onset of strain-induced α′-martensite formation. However, from previous investigations into austenitic CrMnNi steels, it is known that a small strain-induced martensite fraction of 2–5 vol.% already exists in the minimum of the strain hardening curve [ 44 , 45 , 46 ]. Once the minimum in the strain hardening curve was exceeded, the curve increased progressively owing to the strong effect of strain-induced martensite on the strain hardening rate during ongoing tensile deformation (stage II).…”
Section: Discussionmentioning
confidence: 99%
“…[ 2,6 ] As the chemical driving force ΔGγα decreases with increasing temperature, the austenite stability increases which is accompanied by a decrease in the strain‐induced α′‐martensite fraction after tensile test. [ 9,30,35–39 ] Consequently, a martensite volume fraction of less than 1 vol% at 60 °C or no martensite at 100 °C was detected (cf., Figure 1b). It is also known that the formation of strain‐induced martensite is possible from the M d temperature and below.…”
Section: Resultsmentioning
confidence: 99%
“…The used parameter n of the Olson and Cohen fit was 4.5 and agrees with other research results. [ 6,10,30,35,53,56 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several parameters, such as the deformation mode, rolling temperature, and SFE, have been proven to influence the microstructural evolution of austenitic stainless steel. [22][23][24][25][26] Lee et al [27] have reported that strain-induced martensite transformation occurs when the SFE is below 15 mJ m À2 , whereas deformation twinning occurs when the SFE is above 20 mJ m À2 in Fe-Cr-Mn-N-C alloys. Allain et al [28] have indicated that in Fe-Mn-C alloys, martensitic transformation occurs when the SFE is below 18 mJ m À2 , however, deformation twinning is observed when SFE is between 12 and 35 mJ m À2 .…”
Section: Introductionmentioning
confidence: 99%